Parental perceptions of transition from intensive care following a child's cardiac surgery. Issue 3 (10th August 2015) - Obas, Katrina A.; Leal, Jessica M.; Zegray, Michele; Rennick, Janet E.
ABSTRACT: Background: Children with congenital heart disease (CHD) who undergo cardiac surgery are hospitalized in a paediatric intensive care unit (PICU) prior to being transferred to a surgical ward. This is a challenging transition for parents of children with CHD who experience high levels of stress related to their child's illness. Aim: To explore parents' perceptions of the transition from the PICU to the surgical ward following their child's cardiac surgery. Study design: A qualitative descriptive design using semi‐structured interviews was used to explore parents' perceptions of the transfer experience. Methods: All parents of children with CHD who met inclusion criteria were approached to participate. Parents were recruited until data saturation was achieved ( n  = 9). Interviews were audiotaped and transcribed verbatim. Transcripts were coded and thematically analysed concurrently with data collection. Results: Parents described having mixed feelings of happiness and uncertainty upon learning that their child would be transferred to the surgical ward (theme 1). Parents' uncertainty prompted a need to rally for the upcoming transfer, a process in which the nurse was perceived to play an important role (theme 2). Once transferred to the surgical ward, parents described having to come to terms with a new care experience in which they encountered new role expectations and a challenging new environment (theme 3). Conclusion: Emotional reactions to transfer were generally consistent with the literature, although parents in our study did not describe feelings of isolation related to transition as reported elsewhere. We also identified the timing of transfer as a potential source of stress for parents. Parents identified key nursing interventions that helped them to prepare for transfer and come to terms with challenges in their new environment. Relevance to practice: A deeper understanding of parents' transfer experience will facilitate the development of effective nursing interventions to support parents at this time.